Principal Management Strategy in Building an Anti-Bullying School Culture (A Study at SMP Negeri 1 in Sabang City, Aceh Province) - Cut Novayanti; Muhammad Iqbal; Zikrur Rahmad (Lembaga Bale Literasi, 2026)
This study aims to analyze the principal's management strategies in building an anti-bullying school culture at SMP Negeri 1 Sabang City and MTsN 1 Sabang City, and to identify supporting factors, inhibiting factors, and similarities and differences in the strategies implemented in both schools. This study used a qualitative approach with a comparative study design through data collection techniques in the form of interviews, observation, and documentation. The results of the study indicate that the principal's management strategies in building an anti-bullying school culture are implemented through the systematic application of management functions, including planning, organizing, implementing, and monitoring and evaluating. In the planning stage, the principal identifies school needs, formulates program objectives, and develops bullying prevention policies tailored to student characteristics and school culture. The organizing stage is carried out by forming a bullying prevention team involving teachers, homeroom teachers, guidance counselors, the student council (OSIS), the school committee, and parents. The strategy is implemented through various preventive and educational programs such as anti-bullying socialization, integration of empathy and tolerance values in learning, routine character building, and child-friendly school campaigns. Supervision is carried out through reporting mechanisms, gradual case handling, student mentoring, and evaluation with teachers and the school committee. The success of this strategy was supported by the principal's visionary leadership, teacher support, school committee involvement, and parent participation. However, several obstacles remained, such as the lack of written SOPs for handling bullying, the perception that verbal teasing is just a joke, inconsistent enforcement of rules, the influence of social media, and limited supervision outside of school hours. This study also showed that both schools had similarities in implementing management functions and a character-based preventive approach, but differed in the values they used, namely universal character values and religious values. The research findings confirm that effective anti-bullying strategies require strong leadership, systematic management, and collaboration between schools, families, and the community